PENGARUH PENDIDIKAN KESEHATAN DENGAN METODE SIMULASI TERHADAP PENGETAHUAN BANTUAN HIDUP DASAR SISWA SMAN 1 BANJARMASIN - Khalilati, Noor; Huzaifah, Zaqyyah; Daud, Izma; Suwandewi, Alit; Aprilia, Hanura; Wulan, Diah Retno; Azidin, Yustan; Mariani, Mariani; Ahmad, Hairul (Journal of Nursing Invention, 2025)
Cardiac arrest is a condition where the heart suddenly stops beating. This condition causes the heart to lose its function, namely to pump blood throughout the body, so that the brain and other vital organs in the body such as the liver and lungs do not receive blood flow and oxygen. So if there is a delay and inaccuracy in providing help it can have fatal consequences for the victim, causing further brain damage and death. This research aims to determine the effect of providing health education using the simulation method on basic life support knowledge of students at SMAN 1 Banjarmasin. This research uses a quantitative research type with a pre-experimental design with a one group pre-test post-test approach. The population in this study was 372 people with a sample of 80 people calculated using the Slovin formula. Sampling was carried out using a simple random sampling technique. Data were collected using a questionnaire with 19 questions related to knowledge about Basic Life Support with the Wilcoxon Matched Pairs statistical test. The results of statistical tests in this study showed that the ρ value (0.001) <α (0.05) so it can be concluded that there is an influence of health education using the simulation method on the basic life support knowledge of students at SMAN 1 Banjarmasin. It is hoped that students can apply it to emergency conditions such as cardiac arrest.